The risk factors of urinary tract infection among elementary school students in Sleman District, Yogyakarta Special Region - Arya Agustino Purba Pungky Ardhani Suryana Yudha Patria, Tonny Sadjimin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Urinary tract infection (UTI) is the second commonest acterial infection in Indonesian children after respiratory tract infection. In order to establish early diagnosis of UTI, it is important to recognize the risk factors of UTI in children. The aim of this study was to evaluate the associationbetween circumcision, personal hygiene, environmental sanitation, nutritional status, parents’ educational level, socioeconomic status, constipation, and class attendance with incident of UTI and to determine its prevalence in elementary school students in Depok and Ngaglik SubDistricts, Sleman District, Yogyakarta Special Region. It was a case-control study using stratified random sampling. Controls were matched with case groups based on school grade and gender. An early screening of UTI using dipstick was conducted, and continued with urine culture toconfirm microorganims infection. The association between the risk factors and the incident of UTI was evaluated using a questionnaire for the students or their parents. Prevalence of UTI in elementary school students in Sleman District was 9.96% with pathogenic microorganisms namely Klebsiella (44.1%), Echerichia coli (31.2%), and Pseudomonas (24.7%). Circumcision (OR=8.00; 95%CI=2.115-193.91; p=0.039) was statistically significant as protective factor ofUTI. Furthermore, poor personal hygiene (aOR = 4.314; 95% CI = 2.202-8.451; p = 0.000) and poor environmental sanitation (aOR = 2.481; 95% CI = 1.264-4.872; p = 0.008) were the high risk factors of UTI, whereas lower socioeconomic status and lower educational level of theparents were not significant risk factors of UTI. Other factors i.e. poor/fair nutritional status, constipation and class attendance were not risk factors of UTI. In conclusion, the prevalence of UTI in elementary school students in Sleman District is 9.96%. Circumcision is a protectivefactor of UTI, whereas poor personal hygiene and poor environmental sanitation are proven as risk factors of UTI.Keywords: urinary tract infection - risk factors - protective factor - elementary school students- pathogenic microorganism